The demographic factors’ contribution to the High School Student’s level of psychological distress in Malang, East Java - Yuniardi, M. Salis; Widyasari, Dian Caesaria; Putri, Aransha K. N. (Universitas Mercu Buana Yogyakarta, 2023)
Demographic factors contribute to the etiology of psychological distress in adolescents, especially as a mark in identifying the vulnerability of these adolescents to high levels of psychological distress. This study aimed to identify the effects of demographic factors, including age, gender, school origin, and parents' marital status, on the level of psychological distress in adolescents who are studying in high schools in Malang, East Java. This cross-sectional study used the Hopkins Symptoms Checklist 25 (HSCL-25) measuring instrument to measure the level of psychological distress in adolescents and data filling on age, gender, school origin (Public Senior High School/Vocational Senior High School/Islamic Senior High School), and parents' marital status (married, divorced, widow/widower). Eight schools in Malang City were randomly selected to participate in this study. 520 students from eight high schools participated in filling out the questionnaire. The crosstab analysis reports that 53.1% of subjects showed high psychological distress. Based on the results of logistic regression analysis, the gender (OR = 0.55, p = 0.002) and school origin (OR = 0.74, p = 0.027) factors contributed to the level of psychological distress in adolescents who were studying in high schools. Based on the steadiest contribution from the gender factor, female students were 0.55 times more prone to experiencing high psychological distress than males. Thus, developing promotion and prevention programs in high schools regarding mental health and gender-related issues is crucial.